Effects of Power Terms and Thermodynamics on the Contraction of Pinch Radius in Plasma Focus Devices Using the Lee Model - Akel, M.; Ismael, Sh.; Lee, S.; Saw, S. H.; Kunze, Hans Joachim (Springer US, 2016)
The influence of the power terms Joule heating and radiative losses on the pinch radius in plasma focus devices is studied. Numerical experiments were carried out using the Lee model on three plasma focus devices spanning a large range of storage energy (PF400, INTI PF, PF1000) with different filling gases (N, O, Ne, Ar, Kr, Xe). Six possible regimes each characterized by a combination of significant power terms affecting plasma focus dynamics are found and discussed. These six possible regimes are further moderated by thermodynamic effects related to the specific heat ratio SHR of the plasma. In PF1000, the thermodynamic compression effects are clearly apparent in the radius ratio versus pressure curve for nitrogen which with atomic number Zn = 7 is less radiative than neon with Zn = 10, the dominant line radiation being proportional to Zn4. In neon radiative compression at optimum pressure is so dominant that it masks thermodynamic compression in the compression versus pressure graph. Results show that plasma radiation losses enhance the contraction of the plasma focus pinch radius within suitable pressure ranges characteristic of each machine for each gas discussed in this paper. The radiation enhancement of compression increases with the atomic number of the gas.